2019
DOI: 10.1108/f-11-2018-0136
|View full text |Cite
|
Sign up to set email alerts
|

Smart campus tools 2.0 exploring the use of real-time space use measurement at universities and organizations

Abstract: Purpose The purpose of this study is to generate knowledge about the use of smart campus tools to improve the effective and efficient use of campuses. Many universities are facing a challenge in attuning their accommodation to organisational demand. How can universities invest their resources as effectively as possible and not in space that will be poorly utilized? The hypothesis of this paper is that by using smart campus tools, this problem can be solved. Design/methodology/approach To answer the research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…However, as stated by Ref. [ 7 , 8 ], there is a need for better linkage between these aspects. Fig.…”
Section: Academic Buildings and Iot-based Smart Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as stated by Ref. [ 7 , 8 ], there is a need for better linkage between these aspects. Fig.…”
Section: Academic Buildings and Iot-based Smart Toolsmentioning
confidence: 99%
“…Empirical studies that use large data from IoT tools to design interventions for space use management in learning spaces are scarce. The need for more research is underlined in a recent study referring to the vast interest of the facility managers and the variety of possible system configurations, for example, on using different sensors and data sources [ 7 ]. They also identified a knowledge gap on the connection between the technical and management aspects and inferred the need to provide management information that guides the practitioners to use smart tools for space use management [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collected data in this study is related to only one semester although as suggested by [20], in order to reduce m2 footprint, it is better to wait until a smart tool is implemented for an extended period of time. Further studies should also include different stakeholders by investigating the perceptions and preferences of staff and students on booking lecture rooms.…”
Section: Resultsmentioning
confidence: 99%
“…Research on IoT tools in buildings has been more technology-oriented rather than involving different disciplines related to building industry to identify the added value of these systems [19]. Majority of papers on the subject focus on performance criteria such as accuracy for a new system design applied in a small scale [20]. The prominent potential that IoT and big data offer may fundamentally change the operation and management of real-estate in universities [21].…”
Section: Space and Energy Management In Heismentioning
confidence: 99%